(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wireless Sensor Networks (WSN) is rapidly getting more and more important today. Since the WSN require being battery powered. Power consumption is one of the most crucial design issues in WSN nodes. Increasing the WSN nodes lifetime depends on the efficient management of available energy. In this thesis, a low power WSN node with new approach for energy management is introduced. In the proposed WSN node, to achieve energy conservation, the amount of data transmitted was reduced through data compression by lowering the transceiver duty cycle and frequency of data transmissions using an event-driven transmission strategy. In an event-driven transmission strategy data is transmitted only when the data sensed by the sensor is above a particular threshold value, which is identified as event occurs. Power reduction strategies for the different components of WSN node were also applied like gating off power supply of the components. It is gated on only when the components are used.